2019
DOI: 10.47176/mjiri.33.16
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro prostate cancer biomarker detection by directed conjugation of anti-PSCA antibody to super paramagnetic iron oxide nanoparticless

Abstract: There are a few studies that have assessed the oriented conjugation methods (Covalent binding via carbohydrate moieties on the FC region of antibody). The conjugation of anti-hCG antibody to paramagnetic nanoparticles is one of them which was tested successfully. →What this article adds:In this study the oriented conjugation method was done through carbohydrate moieties of the FC domains for anti-PSCA antibody and dextran-superparamagnetic iron oxide nanoparticles for the first time in the world. In comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The intensity of the blue color (resolution) was observed to be higher with a smaller size (20 nm in diameter) of dex-SPION than a larger one (100 nm). The color intensity verified the efficient binding of anti-PSCA antibody-dex-SPION (20 nm) on the cell surface with improved imaging and targeting ability than dexSPION [64].…”
Section: Antibody and Polypeptide-based Detectionmentioning
confidence: 74%
See 1 more Smart Citation
“…The intensity of the blue color (resolution) was observed to be higher with a smaller size (20 nm in diameter) of dex-SPION than a larger one (100 nm). The color intensity verified the efficient binding of anti-PSCA antibody-dex-SPION (20 nm) on the cell surface with improved imaging and targeting ability than dexSPION [64].…”
Section: Antibody and Polypeptide-based Detectionmentioning
confidence: 74%
“…It was essential for clinical staging and marking of invasion area e.g., seminal vesicle, prostate capsule, respectively [62,63]. Farahani et al developed an antibody-binding nanoparticle against PSCA for PCa diagnosis [64]. The major challenge was maintaining the ability of antibodies to bind with antigens.…”
Section: Antibody and Polypeptide-based Detectionmentioning
confidence: 99%
“…Finally, the most important marker that appears to have a potential role in the development of prostate cancer is PSCA. As mentioned earlier, PSCA antigen is a cell surface antigen that can be effective for many immunological strategies [ 43 ].…”
Section: Psca Expression and Polymorphisms In Different Cancersmentioning
confidence: 99%
“…In in vitro studies, overexpression of prostate stem cell antigen (PSCA) was identified in 90% of samples where the ability of mAbs to identify PSCA was significantly increased by the use of conjugate–dextran antibodies with superparamagnetic iron oxide [ 44 ]. As such, the labeled cell produces intense blue color upon binding with anti-PSCA-dextran-superparamagnetic iron oxide [ 45 ]. In non-Hodgkin’s lymphoma (NHL), anti-CD20 polyclonal antibody-radioisotopes/fluorophores conjugated with chitosan has been used for its detection [ 46 ].…”
Section: Current Developmental Status Of Abc In Oncologymentioning
confidence: 99%